Leisure activities, attitudes and satisfaction of youth in the context of Malaysian young partners policy / Mawarni binti Mohamed - Mohamed, Mawarni (2013)
Leisure time and the activities play important roles in the lives of young people in many countries. In Malaysia, the government aspiration on youth development has been presented in Malaysian policies to guide the young generation. The Malaysian National Youth Policy was established to encourage youth involvement in a variety of physical, social, cultural, and community activities. In response to that, Young Partners (YP) Policy was born with the objective to cater for youth needs in leisure activities and to curb immoral social behaviors among them. It promotes the use of leisure time as a means to spiritual, social, and physical development and to foster integration and community involvement among them. This study examines youth participation, attitudes and satisfaction in leisure activities under the Young Partners (Rakan Muda) policy. A multi-model design was used to collect both the quantitative and qualitative data. Using the cluster random sampling technique for quantitative data gathering, self-completed questionnaires were distributed among Young Partners participants. Descriptive and inferential statistical analyses were used to analyze the quantitative data. Qualitative data were gathered from interviews with YP officers regarding their views on the management and the mechanism used in implementing the YP policy in the state of Selangor. Results of the study showed that youth mainly conceptualized leisure as having ‘free time’. The involvement in leisure activities differed between male and female where males involved themselves in more active or sporting activities whereas female were more passive. Findings related to negative activities were relatively small for both sexes and youth seemed to have a positive attitude towards activities under YP policy. However, the upper SES youth have a better understanding of how they can fill their spare time with diversely interesting activities. As far as leisure satisfaction is concerned, ‘aesthetic’ aspect stands out and they also agreed that ‘relaxation’ gave them the most satisfaction. Qualitative data showed that the government has been prescriptive in setting the structure in the management aspect. Moreover, the YP mechanism through organized leisure was seen as one way to achieve the government’s goals and aspirations towards diverting youth from social ills. This study suggests that leisure education should be introduced in schools’ curriculum and the provision of quality government sponsored leisure activities should be available for youth positive social changes following the aspiration of the nation, together with more systemize leisure programs in accordance with youth leisure needs.